Hemoglobin Evanston (alpha 14 Trp----Arg). An unstable alpha-chain variant expressed as alpha-thalassemia. - Honig, G R (1984)
A new hematologic syndrome with phenotypic features of mild Hb H disease was identified in three children from two unrelated black American families. Erythrocytes from each of these children contained Hb H (beta 4) and Hb Barts (gamma 4), as well as a slowly migrating hemoglobin fraction that made up 7-10% of the total hemoglobin. The parents of the affected children all showed mild thalassemia-like changes, with one of the parents in each family also expressing the variant hemoglobin; in the latter individuals the mutant alpha-chains made up less than 2% of the total, and were present mainly or exclusively in combination with delta-chains in the form of a slowly migrating Hb A2. Purified Hb Evanston showed an increased oxygen affinity, but its Bohr effect, cooperativity, and 2,3-diphosphoglycerate effect were normal. The mutant hemoglobin appeared to have normal stability to heat and to isopropanol, and the stability of its alpha-chain in an extended time course synthesis study also appeared to be similar to that of alpha A. However, the results from short-term globin synthesis studies, and from mRNA translation in vitro, suggest that the two types of alpha-chains were synthesized at relatively equal rates, with a major fraction of the newly synthesized variant alpha-chains undergoing rapid catabolism. The hematologic data taken in combination with DNA hybridization and globin synthesis findings indicate that the proposita in each of these families has the genotype--, alpha A/--, alpha Ev. These observations suggest that two separate mechanisms are contributing to the alpha-thalassemia-like expression of Hb Evanston : the newly synthesized alpha EV-chains are unstable and are subject to early proteolytic destruction; and the mutant alpha-allele is linked to an alpha-globin gene deletion.